Perbandingan Psikoanalisis Novel Sunyi Adalah Minuman Keras dengan Novel Convenience Store Woman - Tiara Tri Dewi; Syahrul Ramadhan; Tressyalina Tressyalina; Afnita Afnita (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This paper examines the comparison between two literary works in the form of novels originating from Indonesia and Japan. The novels under study are "Sunyi Adalah Minuman Keras" by Sapardi Djoko Damono and "Convenience Store Woman" by Sayaka Murata. The issue discussed revolves around the personality system proposed by Sigmund Freud, namely id, ego, and superego, present in the two main characters of the novels. This research employs a qualitative research method with a comparative literary approach. The data in this study consist of words or sentences found in the novel "Sunyi Adalah Minuman Keras" and "Convenience Store Woman" involving the characters and related to Sigmund Freud's psychoanalytic theory. The data collection technique used was reading and note-taking. The research findings indicate that "Sunyi Adalah Minuman Keras" by Sapardi Djoko Damono and "Convenience Store Woman" by Sayaka Murata share many similarities in behavior between the two characters when viewed through Sigmund Freud's psychoanalytic theory, consisting of id, ego, and superego. The character Rara is more dominated by the id system, while Keiko is more dominated by the ego system.